Past Tense Marking in the Spontaneous Speech of Preschool Children Who Do and Do Not Stutter - Bauman, Jessica (2012)
PURPOSE: The aim of this study was to identify whether different patterns of errors exist in irregular past-tense verbs in children who stutter (CWS) and children who do not stutter (CWNS) METHOD: Spontaneous language samples of thirty-one age- and gender- matched pairs of children (total N = 62) between the ages of 24 months and 59 months were analyzed. RESULTS: Results indicated that children who do and do not stutter over-regularize irregular past-tense verbs (i.e., saying runned for ran) with comparable frequency. However, two nonsignificant trends which suggest possible intra-group differences were noted. First, irregular pasttense verbs represented a greater portion of total verbs for CWS than for CWNS. Second, CWS appeared to double-mark (i.e., say ranned for ran) more often than CWNS. Results are discussed in light of theories about the acquisition of the irregular past-tense and about differences in language skills between CWS and CWNS.